Assessment of the Crack Level in Silo Foundations Due to Settlement - Malinda, Yosie; Vidayanti, Desiana; Citra, Zel (Universitas Negeri Padang, 2024)
A silo is a structure used to store bulk materials (bulk materials). Silos are generally used in agriculture as storage for grains and animal feed. The foundation silo must be designed to withstand the forces generated and accommodate the movements transmitted to the structure and foundation by the seismic ground motion design. The dynamic properties of the soil, the anticipated ground motion, the design basis for the strength and energy dissipation capacity of the structure, and the dynamic characteristics of the soil should be included in determining the foundation design criteria. In PT X, SILO structure serves as a place for livestock feed production, with the hope that it can last for a relatively long time. The condition of the existing SILO structure is currently some cracks in several parts of the piles and the bottom slab. The results of the visual inspection in the field regarding the condition and level of cracking in the silo foundation were compiled into a matrix inspection table using four categories: category 1 indicates no repairs needed, category 2 marked in green, represents an acceptable cracking condition with minor repairs, category 3 marked in yellow indicates moderate cracking that requires attention, and category 4 marked in red signifies major cracking or unacceptable conditions that require structural repairs. The results of the field inspection indicate that approximately 57% of the concrete slab foundation of the silo requires needs attention or repair. The condition of the plate/slab structure has some cracks measuring 0.3mm - 0.5mm, but injection and patching have been carried out. As for the condition of the silo foundation, about 30% requires needs attention and repair as well.